Formation and Evolution Mechanisms of Severe Haze Pollution in the Sichuan Basin, Southwest China - Xianyu Yang; Yaqiong Lu; Xinsheng Zhu; Jianjun He; Qi Jiang; Kai Wu; Haolin Wang; Xiaoling Zhang; Shigong Wang (Aerosol and Air Quality Research)
Abstract Severe haze episodes are important environmental issues, and the rapid formation and evolution mechanisms of such episodes over complex terrain remain poorly understood. The Sichuan Basin (SCB) periodically experienced heavy haze pollution during the winter of 2016, with the maximum regional average PM2.5 concentration reaching almost 120 µg m −3. In this study, we characterize a severe haze episode in the SCB from 20 to 30 January 2017 using comprehensive measurements and model analyses. The evolution of this severe episode shows clear stages, with gradual PM25 increases under stagnant weather conditions in Stage I (aerosol accumulation stage) and with explosive PM25 increases mainly associated with cross-border transport from the southern SCB in Stage III (rapid formation stage). The process analysis results indicated that primary emissions and aerosol processes were the major sources of PM2.5 in these urban regions, whereas vertical transport and dry deposition generally acted as sinks of PM2.5. In the presence of southwesterly synoptic winds, the aerosols emitted from the southern SCB were transported to Chengdu and the surrounding areas through horizontal transport and accounted for 66% of the PM2.5 concentration in Chengdu during Stage III. Our results reveal the detailed formation mechanism of a severe haze episode in the SCB under the effects of regional transport and synoptic forcing patterns to improve the understanding of haze formation in areas with complex terrain.